Maximal oxygen uptake of male professional soccer players, 2012-2015, at the end of four preseasons training - Santos Silva, Paulo; Pedrinelli, André; José Hernandez, Arnaldo; D´Andrea Greve, Júlia Maria; Yoshio Nakano, Eduardo; Veiga Guimarães, Guilherme (Open Science Journal, 2021)
Purpose: We hypothesized that the aerobic capacity of soccer players was well developed and maintained during the competitive season and that a short rest period in the off-season would not be sufficient to significantly affect V̇O2max in these players. Methods: A total of 211 soccer athletes (age range, 17-34 years) being 71 professional juniors and 113 professional adults were compared with a control group of 27 non-professionals soccer players. All players performed cardiopulmonary exercise testing on a treadmill. Results: The results showed that a large number of soccer players had V̇O2max levels incompatible with the status of professional athletes in this sport. The results between the players were: The player’s juniors presented average V̇O2max (56.2 mL.min-1.kg-1) significantly higher (P < 0.05) of that the professional players (53.3 mL.min-1.kg-1) and controls (amateur, 50.4 mL.min-1.kg-1). However, a large number of the adult (67%) and juniors (42%) professionals players presented values of V̇O2max near to the values covered for the control group. Conclusions: The study verified a great number of soccer players, considered of the elite, with values below that it is recommended for players of this competitive level. It seems that preseason training was not enough to achieve compatible V̇O2max levels for most players.